AN OBVERVATIONAL STUDY ON A BATAK ENGLISH LEARNER IN CONSONANT SOUND PRODUCTION - Yuliyanto Sabat (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2019)
This article reports on the result of a study aiming to describe what difficulties experienced by Batak English learner in consonant sound production and the factors which cause him difficult to produce those sounds. The study was conducted to Batak English learner who is still taking pronunciation course in the first semester in the English study program at one of private universities in East Java, Indonesia. The study used a qualitative case study research design with the data collected from the analysis of students’ English consonants production and interview. The findings showed that all sounds of voiceless dental frecative consonant [θ] in initial position were pronounced into voiceless alveolar stop consonant [t] while the research participant was pronouncing the sound of voiced dental frecative consonant [ð], he mispronounced the sound into voiced alveolar stop consonant [d] in both initial and medial position. The sound of voiced alveolar affricate consonants [dʒ] was pronounced appropriately while voiceless alveolar affricate consonant was pronounced into voiceless alveolar fricative consonant [s]. The factors which cause the participant find it difficult to learn pronunciation were afraid of making mistakes, limited time to repeat it at home, and habit.